Implementation of Reproductive Health Services for Female Prisoners at Class IIA Women's Penitentiary in Bandung - Elhana Theodora Simanungkalit; Dedah Ningrum; Iis Aisyah (Viva Medika, 2024)
A convict is someone who is being rehabilitated by a state institution. However, prisoners have the right to good health, including reproductive health. This research aims to describe the implementation of reproductive health services for female prisoners at the Class IIA Women's Penitentiary in Bandung. This study uses a qualitative method with a phenomenological approach. There were 5 participants in this study who were determined using purposive sampling techniques according to the inclusion and exclusion criteria. The results of this study describe six themes: prevention of infectious diseases and non-communicable diseases (NCDs) through routine health education/screening, improving healthy lifestyles for female prisoners through regular exercise, menstrual hygiene services for female prisoners in prisons, providing balanced nutrition for prisoners' reproductive health, efforts to overcome stress for female inmates, and nurturing services from correctional officers in preventing sexual violence.